Security Implications of the Anthropology of Āyatullāh Jawādī Amulī - Najaf Lakzāī (حکمت اسرا)
During the years after the victory of the Islamic Revolution of Iran, islamization of humanities, including security sciences, has been a primary concern. The Transcendent Wisdom has a high capacity to appear in humanities and security sciences. In recent years, security studies and sciences have made good progress in our country; however, no considerable effort has been made to describe security issues relying on the principles of Islamic Philosophy, particularly Transcendent Wisdom. The present article is aimed at presenting implications and security aspects of anthropology of the Muslim jurist and theologian of Transcendent Wisdom, Āyatullāh Jawādī Amulī. This article argues that on the basis of foundations of Transcendent Wisdom, particularly anthropological principles which constitute the central issue of this study, we should speak of “security sciences” rather than “the science of security”. This is because according to any anthropological foundation, a specific security science is produced that may variously be called transcendent, conventional and common.